From Handmaidens to POSH Humanitarians: The Case for Making Human Capabilities the Business of I-O Psychology. Issue 3 (13th June 2017) - Gloss, Alexander; Carr, Stuart C.; Reichman, Walter; Abdul-Nasiru, Inusah; Oestereich, W. Trevor
Abstract : Industrial-organizational (I-O) psychology has begun to shed its reputation as a handmaiden to corporate and managerial interests, in part, through its engagement with humanitarian concerns. However, as highlighted by recent commentary, I-O psychology still has a decidedly POSH perspective on the world; that is, it has focused on Professionals who hold Official jobs in a formal economy and who enjoy relative Safety from discrimination while also living in High-income countries. This POSH perspective reflects an underlying bias away from people living in multidimensional poverty. We empirically illustrate some of the connections between a POSH perspective and poverty by reviewing 100 years of research in I-O psychology, and then we make a case for why a neglect of people living in poverty undermines the discipline's science, its practice, and its humanist charge. As moral justification for greater engagement with humanitarian concerns and as a guide to navigate the difficult ethical quandaries involved in doing so, we suggest that I-O psychologists should consider the capability approach. We discuss the concept of human capabilities, relate it to I-O psychology, and demonstrate its utility in the form of three hypothetical scenarios. Perhaps our most controversial claim is that there is a moral imperative for I-O psychology to overrepresent people living in the deepest forms of poverty in both its science and practice.